The role of diagnostic ability in markets for expert services - Fang Liu; Alexander Rasch; Marco Schwarz; Christian Waibel (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
In credence goods markets, experts have better information about the appropriate quality of treatment than their customers. Experts may exploit their informational advantage by defrauding customers. Market institutions have been shown theoretically to be effective in mitigating fraudulent expert behavior. We analyze whether this positive result carries over to when experts are heterogeneous in their diagnostic abilities. We find that efficient market outcomes are always possible. However, inefficient equilibria can also exist. When such inefficient equilibria are played, a larger share of high-ability experts can lead to more inefficiencies relative to the efficient equilibria.
Keywords: D82; L15; 330; Credence good; Diagnosis; Expert; Fraud; Overtreatment; Undertreatment